Myosteatosis is not associated with complications or survival in HCC patients undergoing transarterial embolization. (March 2023) - Masetti, C.; Pugliese, N.; Lofino, L.; Colapietro, F.; Ceriani, R.; Lleo, A.; Poretti, D.; Pedicini, V.; De Nicola, S.; Torzilli, G.; Rimassa, L.; Aghemo, A.; et al.
Abstract : Background and aims: Alterations in nutritional and metabolic status, in particular sarcopenia, have been extensively associated with a poor prognosis in cirrhotic patients regardless of the etiology of liver disease. Less is known about predictive value of myosteatosis, defined as pathological fat infiltration into the skeletal muscle, in this context. Methods: We retrospectively analyzed a cohort of 151 cirrhotic patients with unresectable hepatocellular carcinoma (HCC) who underwent their 1 st trans-arterial embolization (TAE) between March 1st 2011 and July 1st 2019 in our Institution. Demographic, clinical and biochemical data were collected. Sarcopenia was assessed using the L3-SMI method. We calculated myosteatosis with a dedicated segmentation suite (3D Slicer), using a single slice at an axial plane located at L3 and calculating the IMAC (Intramuscular Adipose Tissue Content Index). The sex-specific cut-off values for defining myosteatosis were IMAC > -0.44 in male and > -0.31 in female. Results: In our cohort of 151 patients, 115 (76%) patients were included in the myosteatosis group; 128 (85%) patients had a coexistent diagnosis of sarcopenia. Patients with myosteatosis were significantly older and showed higher BMI than patients without myosteatosis: male gender and alcoholic or metabolic-related cirrhosis were most represented in the myosteatosis group. Myosteatosis was not associated with different HCC burden, length of hospitalization, complication rates and readmission in the first 30 days after discharge. Overall survival was not influenced by the presence of myosteatosis. Conclusions: Myosteatosis didn't significantly affect the main outcomes of cirrhotic patients with HCC undergoing locoregional treatments.